Office Hours as Dialogic Pedagogy: A Reflective Study of Mentoring International Students in First-Year Composition - Robert mathew (JET (Journal of English Teaching), 2026)
This reflective practitioner study examines the role of office hours as a site of pedagogical mentoring for international students in First-Year Composition at U.S. universities. Drawing on five years of experience as a domestic PhD student and Graduate Teaching Assistant at Wayne State University, the study responds to an initial instructional challenge in which written and peer feedback alone failed to support international students’ rhetorical development, despite their strong grammatical proficiency. Grounded in scholarship on written feedback, grading, and culturally responsive pedagogy, the paper argues that feedback is not inherently transparent and must be mediated through dialogue to become meaningful. Using reflective journals, student performance trends, office-hour interactions, and anonymized student feedback as data, the study demonstrates how intentional mentoring during office hours functioned as a dialogic space for translating feedback, clarifying genre expectations, and building trust. Findings show substantial improvement in students’ writing performance, confidence, and engagement. The study highlights office hours as an equity-oriented pedagogical practice and offers implications for composition pedagogy and GTA training.